PENGARUH NILAI TUKAR RUPIAH, INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP UTANG LUAR NEGERI INDONESIA TAHUN 2000-2017 - Sofian Ibrahim; Wahyu Hidayat; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2019)
The purpose of this study was to analyze how the effect of exchange rate of rupiah, inflation and Economic Growth on Foreign debt in Indonesia in 2000-2017.The instrument Analysis used multiple linear regression method with OLS (ordinary least squares) method by using time series data. The method test using  the classical assumption test and statistical test.From the analysis results obtained that the effect of exchange rate of rupiah is has positively effect and inflation have a negative effect while Economic Growth have a negative effect. Simultaneously of all these variables have a significant effect on Foreign debt in Indonesia. The conclusion of this reserch explains that all of variables, exchange rate of rupiah and Economic Growth variables have a significant postive effect on Foreign debt, and the variable that negatively effect on Foreign debt in Indonesia is inflation variable.